1982
DOI: 10.1679/aohc.45.385
|View full text |Cite
|
Sign up to set email alerts
|

Fine structural aspects of inverted follicles in cultured porcine thyroids.

Abstract: Summary. Inversion of thyroid follicles takes place constantly when they are isolated by digestion and cultured in suspension in Eagle's medium containing fetal calf serum without TSH.Most inverted follicles are spherical in shape. The polarity of the follicle epithelial cell is inverted. The luminal surface loses its microvilli, while the outer surface toward the cultured medium protrudes numerous microvilll, the zonula occludens consisting of 3-8 strands moving from the luminal end to the outer end (culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In the other type of inversion, which is observed in thyroid follicles (Miyagawa et al . ) and in envelopes consisting of MDCK cells (Wang et al . ), the closed envelopes are suspended in culture medium and invert the apical–basal polarity of their epithelial cells.…”
Section: The World Of Epithelial Sheetsmentioning
confidence: 99%
“…In the other type of inversion, which is observed in thyroid follicles (Miyagawa et al . ) and in envelopes consisting of MDCK cells (Wang et al . ), the closed envelopes are suspended in culture medium and invert the apical–basal polarity of their epithelial cells.…”
Section: The World Of Epithelial Sheetsmentioning
confidence: 99%
“…It has been shown that the cell polarity of isolated thyroid follicles obtained by the enzymatic digestion of collagen is inverted when they are cultured in a medium containing 5-10% fetal calf serum (NITSCH and WOLLMAN,1980;GARBI and WOLLMAN,1982;MIYAGAWA et al, 1982MIYAGAWA et al, ,1983KITAJIMA et al, 1985). In this case, the microvilli and the zonula occludens move to the culture medium side.…”
Section: Discussionmentioning
confidence: 99%